Dialektika Maddah Dalam Bencana Alam Gorontalo - Hanapi, Kiky; Panigoro, Muhammad Rizal (LPPM IAIN Sultan Amai Gorontalo, 2024)
This qualitative research seeks to examine the relation and implicaton of maddah (da’wah teaching materials) to discover new understandings of Islamic teachings especially on the issues of natural disaster occured in Gorontalo. Data were collected through observation and in-depth interviews to the preachers, natural disaster victims, and the members of Indonesian Ulema Council of Gorontalo (MUI). This research reveals that there ara at least two main argument of maddah in responding natural disasters. In the first stream, there is maddah that focuses on how natural disaster should be coped with human repentances to the God due to their exploitative actions toward the natural balances; while on the other hand, a madah that moves beyond boundaries of doctrines and ask for direct actions to save the earth. Built on the scholarship of dialectical framework, this paper argues that the difference between maddah teachings can be explained by contextualizing the issues of natural disaster through three primary principles: akidah, sharia and akhlaq. In praxis, this maddah’s vision then manifests in the spirit of natural disaster advocacy such as mutual aid, climate awareness and justice, caring and other collective actions that can guarantee safety as a serious devotion to the God.